Developing home stay tourism in Ban Bang Pat, Changwat Phang-Nga - Nalinporn Boonrodrak (Prince of Songkla University, 2015)
Thesis (M.B.A. (Hospitality and Tourism Management (International Program)))--Prince of Songkla University, 2012